Writing Treatment for Severe Aphasia: Who Benefits? - Beeson, Pélagie M.; Rising, Kindle; Volk, Jennifer (Journal of Speech, Language & Hearing Research, 2003)
Writing treatment that involved repeated copying and recall of target words was implemented with 8 individuals with severe aphasia in order to discern the best candidates for the treatment. Four of the 8 participants had strong positive responses to the copy and recall treatment (CART), relearning spellings for 15 targeted words during 10 to 12 weeks of treatment and up to 5 additional words during a month-long homework-based program. Of the 4 other participants, 3 learned the spellings of some target words but failed to reach criterion, and 1 had a poor treatment outcome. Insights regarding possible factors that limited success were gained by examination of individual responses to treatment as well as performance on the pretreatment assessments of semantic, phonological, and orthographic processes. Among the factors associated with success were (a) consistent, accurate completion of daily homework, (b) a relatively preserved semantic system, (c) the ability to discern words from nonwords, and (d) adequately preserved nonverbal visual problem-solving skills. Aphasia severity and minimal pretreatment spelling abilities did not necessarily limit the response to treatment. Participants with positive treatment outcomes demonstrated improved spelling of target words following repeated copying within a single treatment session, and accurately completed daily writing homework. Thus, pretreatment assessment and stimulability within initial treatment sessions provided indications of likely outcome. Reprinted by permission of the publisher.